Key determinants of time to 5 m in different ventral swimming start techniques - Peterson Silveira, R.; Stergiou, P.; Figueiredo, P.; de S. Castro, F.; Katz, L.; Stefanyshyn, D. J. (European Journal of Sport Science, 2018)
The aim of this study was to determine the biomechanical parameters that explain ventral start performance in swimming. For this purpose, 13 elite swimmers performed different variants of the ventral start technique. Two-dimensional video analyses of the aerial and underwater phases were used to assess 16 kinematic parameters from the starting signal to 5 m, and an instrumented starting block was used to assess kinetic data. A Lasso regression was used to reduce the number of parameters, providing the main determinants to starting performance, revealing different combinations of key determinants, depending on the variant (r² = 0.90), with flight distance being the most relevant to all variants (r = -0.80; p < .001). Also, special attention should be given to the total horizontal impulse in the grab start (r = -0.79; p < .001) and to the back foot action in the track and kick starts (r = 0.61; p < .001). In addition, we provide two equations that could be easily used to predict starting performance by assessing block time and flight time (r² = 0.66) or block time and flight distance (r² = 0.83). These data provide relevant contributions to the further understanding of the biomechanics of swimming starts as well as insights for performance analysis and targeted interventions to improve athlete performance.